Establishment of an RPA-CRISPR/Cas12a combined diagnostic system for Pneumocystis jirovecii pneumonia. - Yun Wu; Yuhan Shao; Wei Li; Ying Yu; Xia Rao; Jingyi Li; Nicholas R Waterfield; Guowei Yang (PLoS Neglected Tropical Diseases)
Pneumocystis jirovecii causes severe pneumonia in immunocompromised individuals, leading to high mortality and an economic burden. There is a need for early detection methods suitable for low-resource settings and rapid point-of-care diagnostics. This study developed a detection method using Recombinase Polymerase Amplification (RPA) followed by CRISPR/Cas12a with fluorescence detection. The RPA primers and CRISPR-derived RNAs (crRNAs) were specifically designed to target the mitochondrial small subunit rRNA (mtSSU rRNA) gene of P. jirovecii. A total of 83 clinical samples were tested using this method, including 39 confirmed and 44 suspected cases of P. jirovecii infection. The combination of crRNA5 and crRNA6 demonstrated higher sensitivity compared to the current real-time PCR detection method, with a limit of detection (LOD) of 1 copy per reaction and showed no cross-reactions with other respiratory pathogens. The concordance of this method was validated with both infected and non-infected patients. In conclusion, the method developed in this study potentially provides a highly sensitive and rapid tool suitable for the early and on-site detection of P. jirovecii pneumonia. Furthermore, this method holds potential applications for the detection of other human pathogens, representing a significant advancement in diagnostic capabilities for low-resource settings.